Gastrointestinal stromal tumors: Factors affecting prognosis and single-center surgery results (Annals of Medical Research, 2021)
None
Keywords: Mesenchymal Tumor; Tyrosine Kinase; Wedge Resection; Colorectal; Imatinib.